TEACHERS' PERSPECTIVES ON THE USE OF VIRTUAL INFORMAL ENVIRONMENTS IN THE PANDEMIC CONTEXT - Türkmen, Hakan; Kaplan, Gülçin; Sürgit, Cansu (International Journal of Education, 2024)
Since the pandemic situation, there has been a need for enacting student-centered teaching activities to make distance education more effective. "Informal Learning Environments" activities are suitable opportunities to meet this need and positively affect students in many aspects. The use of "Virtual Informal Environments" (VIE) is important during the pandemic situation in this case. The purpose of this research is to examine the teaching processes of teachers using VIEs during the pandemic situation and to make general judgements in the context of teaching processes using VIEs according to their status of taking or not taking courses on teaching in informal environments. In the study, the descriptive research method was used. The study group of the research consists of 93 teachers and it was determined by using the "Easy Access Sampling" method. Eight open-ended question forms were applied to the participants. The data were evaluated with the Content Analysis Method. The results showed that the informal science education (ISE) course-taken teachers used VIEs more consciously than the non-course-taken participants. By focusing on the achievements in the curriculum, teachers planned to use VIEs and integrate these environments into their lessons by adopting a student-centered approach. In the evaluation studies after the teaching activities using VIEs, it was concluded that they tend to evaluate the achievements, not the learning process.